2008
DOI: 10.4049/jimmunol.181.4.2683
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte gp130 Expression Is Critical for the Control of Toxoplasma Encephalitis

Abstract: Toxoplasma gondii infects astrocytes, neurons and microglia cells in the CNS and, after acute encephalitis, persists within neurons. Robust astrocyte activation is a hallmark of Toxoplasma encephalitis (TE); however, the in vivo function of astrocytes is largely unknown. To study their role in TE we generated C57BL/6 GFAP-Cre gp130fl/fl mice (where GFAP is glial fibrillary acid protein), which lack gp130, the signal-transducing receptor for IL-6 family cytokines, in their astrocytes. In the TE of wild-type mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 43 publications
1
81
0
Order By: Relevance
“…Astrocytes are targeted by T. gondii in vitro (Fagard et al, 1999;Fischer et al, 1997), and in vivo studies have demonstrated that tachyzoites of T. gondii extensively infect astrocytes in the early period during cerebral invasion (Bjerkas, 1990;Gonzalez et al, 2007). Activated astrocytes perform an important regulatory role in TE by restricting lesions and preventing necrosis and parasite replication (Wilson and Hunter, 2004;Drögemüller et al, 2008;Stenzel et al, 2004). Studies have demonstrated the importance of GFAPpositive astrocytes in survival mechanisms in TE.…”
Section: Discussionmentioning
confidence: 98%
“…Astrocytes are targeted by T. gondii in vitro (Fagard et al, 1999;Fischer et al, 1997), and in vivo studies have demonstrated that tachyzoites of T. gondii extensively infect astrocytes in the early period during cerebral invasion (Bjerkas, 1990;Gonzalez et al, 2007). Activated astrocytes perform an important regulatory role in TE by restricting lesions and preventing necrosis and parasite replication (Wilson and Hunter, 2004;Drögemüller et al, 2008;Stenzel et al, 2004). Studies have demonstrated the importance of GFAPpositive astrocytes in survival mechanisms in TE.…”
Section: Discussionmentioning
confidence: 98%
“…Streptavidin-biotin-peroxidase complex method. Bars 50 μm the negative aspects of reactive astrogliosis (Silver and Miller 2004), several studies of animal models describe the protective role of reactive astrogliosis within the CNS, such as the elimination of reactive oxygen species, BBB repair and the limitation of dissemination of inflammatory cells and infectious agents throughout the CNS (Bush et al 1999;Chen et al 2001;Drögemüller et al 2008;Faulkner et al 2004;Voskuhl et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Severe reactive astrogliosis can result in the formation of a compact glial scar. Scar tissue is observed lining the borders of the site of CNS insult and is believed to act as a neuroprotective barrier to cells of the immune system and infectious agents [117][118][119][120].…”
Section: Reactive Astrogliosismentioning
confidence: 99%